Studi “Melek Pancasila” berbasis toleransi tri kerukunan umat beragama di Desa Balun Kecamatan Turi Kabupaten Lamongan - Hanafi, Hanafi (Universitas Negeri Malang, 2023)
This research-based study aims to analyze how the values of Pancasila are implemented, especially the portrait of the value of unity and integrity which is manifested in the